Enhancing State Civil Apparatus (ASN) Competencies at KPU Secretariat through the SiMPEL Application - Ricky Febriansyah; Ana Husnayanti; Dani Mahdi (Institut Pemerintahan Dalam Negeri, 2026)
The shift towards a merit-based system in State Civil Apparatus (ASN) management demands integrated learning governance, especially in archipelagic regions. The General Elections Commission (KPU) responded by developing the Training Management Information System (SiMPEL). This study analyzes SiMPEL's utilization for KPU Secretariat ASN in the Bangka Belitung Islands Province, focusing on Learning Hour (JP) fulfillment, cross-agency collaboration, and algorithmic leadership. Using a descriptive mixed-methods approach, data were collected through purposive sampling of 42 ASNs (questionnaires), interviews with HR officials, and document reviews, analyzed using descriptive statistics and content analysis. The results show that SiMPEL is highly effective in operationalizing the merit system, evidenced by a JP monitoring score of 3.64 and a 100% account adoption rate. The availability of 19 cross-agency e-learning clusters successfully eliminated geographical barriers. However, the implementation of algorithmic leadership is hindered by the manual certificate input process, which received a very low score (1.79), potentially causing data incompleteness (garbage in, garbage out). In conclusion, while SiMPEL has successfully digitized mandatory JP fulfillment, it has not fully transformed into a strategic decision-making tool. This study recommends automating system integration and decentralizing data access (Role-Based Access Control) to regional KPU offices.